La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Fondation Musicaction, 2022)

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Genre, rap et enjeux de la visibilité dans l'espace public des rappeuses à Montréal : de la gestion de l'apparence physique pour être reconnue en tant qu'artiste - Lesacher, Claire (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Situer les femmes dans l'Electronic dance music culture (EDMC) à Montréal, entre 1950 et 1955 : premier survol - Van Vliet, Kiersten (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Quadruple défi pour les artistes femmes, immigrantes et allophones : Le cas du premier Sarau das Minas Montréal - Vasconcellos de Carvalho, Dalila (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"-- Author's abstract

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)

L'improvisation jazz : une pratique fondamentale dans le processus de reconnaissance des musiciennes de Montréal - Champagne, Lysandre (Université du Québec à Montréal, 2019)
À partir des dimensions spatiale, temporelle et musicale, ce mémoire expose les modalités de reconnaissance des improvisatrices de jazz dans les jam-sessions de Montréal. En se référant au concept de Jeu chez Mead, l'autrice montre que l'authentification des musiciennes en situation d'improvisation est le produit de la communication mise en forme par ce type d'interaction. Toutefois, le contexte des jam-sessions montréalais maintient un «entre-soi» masculin défavorable à la reconnaissance des musiciennes comme improvisatrices distinctes dans ce jeu musical. Ainsi, l'improvisation dans ces événements de jazz participe à la reconduction des inégalités de genre.

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

Festivals de musique québécois : où sont les femmes ? - Croteau, Laurianne (Ici Radio-Canada, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 1 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)

Sexisme en musique : des trucs pour s’assurer une programmation paritaire et inclusive – Partie 2 - Daguzan Bernier, Myriam (Gazette des femmes, 2019)
Solutions constructives pour des rendez-vous musicaux plus vivants, diversifiés et… paritaires!

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

Les épreuves du travail musical : la persévérance des musiciens et musiciennes au Québec - Lavoie-Ricard, Olivier (Université de Montréal, 2018)

Le son au théâtre et en danse contemporaine : les principes conceptuels récurrents de ma pratique - Tobin, Nancy (Université du Québec à Montréal, 2017)
Ce mémoire-création porte sur la conception sonore pour le théâtre et la danse contemporaine. Il vise à fournir des connaissances qui puissent faciliter l'intégration du son au sein d'une création scénique. La recherche dont il est question ici se concentre uniquement sur les aspects conceptuels et non techniques, toutes deux intrinsèques au processus de création du son. Me basant sur mon expérience de concepteure sonore, plus précisément à partir de l'étude de mes notes de chantier de création entre 1999 et 2014, je dégage dix principes récurrents qui indiquent des conditions optimales pour concevoir le son. Ce mémoire-création est l'analyse d'une approche personnelle et le processus méthodologique a été autopoïétique et heuristique. L'étude se présente en trois sections. La première s'intéresse aux récits des processus de création où chaque principe émerge à partir de l'expérience qui est racontée. Dans la deuxième section, les principes s'explicitent davantage au travers l'étude de textes sur la conception du son. Un corpus d'auteurs, surtout des praticiens de la création sonore, est déterminé pour cette partie. Un livret compose la troisième section. Il incarne la partie « création » de ce mémoire. Il s'agit encore de préciser les principes, mais cette fois au travers de dix lettres fictives, destinées à des étudiants-es. Chaque lettre, dont le sujet est un problème rencontré en cours de processus de création, vise à expliquer un principe dans un contexte concret. Le titre du livret est La conception sonore selon Nancy Tobin 01. Mon nom apparaît dans le titre pour signifier qu'il est surtout question de mon approche personnelle. La mention des chiffres « 01 » indique que le livret démarre une série où d'autres personnes conceptrices sont invitées à écrire sur leur propre expérience. Peu de textes sur la conception sonore - sur l'expérience concrète du faire - existent. Ce mémoire-création vise à combler en partie cette lacune et à inviter d'autres créateurs à écrire sur leur pratique. L'expression par le sonore est riche et diversifiée. Plus les pratiques seront partagées et diffusées, plus il sera possible de multiplier les possibles de l'espace de l'écoute.

Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.

Inégalités et minorisation des identités chez les femmes artistes dans la francophonie canadienne - Robineau, Anne (Nouvelles perspectives en sciences sociales : revue internationale de systémique complexe et d'études relationnelles, 2013)
Even if women artists are wishing for recognition of their work, independently from their gender, language and belonging to a cultural group, their practices conditions are sometimes linked to these statuses. Through a sociodemographic study of French Canadian artists, we will analyze more specifically the data on women artists. We will show that, even if they have a higher education than man, women artists usually are considerably less paid for their services. We will also try to understand if minorization processes of women from professional artistic francophone communities can explain some gender inequalities and how the production of identity discourses (women, francophonie, linguistic minority) reinforce tensions between art and the identity perspective.
Keywords: Artiste; Artists; Canadian Francophonie; femmes; francophonie canadienne; inequalities; inégalités; minorisation; minorization; women

De la cuisine au studio - Lupien, Anna (Éditions du remue-ménage, 2012)
De la cuisine au studio explore les parcours de douze artistes issues de trois générations différentes : femmes signataires du manifeste Refus global en 1948, premières cinéastes qui ont œuvré à l’ONF dans les années 1970 et artistes médiatiques impliquées au Studio XX. À partir d’entrevues avec les artistes, Anna Lupien pose un regard sociologique sur l’expérience de créatrices qui ont investi l’art en tant qu’espace d’expression dans la sphère publique. De quelle façon ont-elles élaboré des stratégies créatives et par le fait même donné corps à des transformations sociales engendrées par le mouvement féministe, notamment en ce qui a trait à la conciliation travail-famille ? Comment ont-elles intégré des milieux artistiques qui ne leur étaient pas ouverts d’emblée ? Comment se sont-elles engagées pour le bien commun à travers leur parcours artistique ? Les histoires de ces artistes – Madeleine Arbour, Christine Brault, Mireille Dansereau, Dorothy Todd Hénaut, Stéphanie Lagueux, Bérengère Marin-Dubuard, Helena Martin Franco, Terre Nash, Anne-Claire Poirier, Françoise Riopelle, Bonnie Sherr Klein et Françoise Sullivan – témoignent des luttes inachevées du mouvement féministe et des brèches qu’elles ont pratiquées dans l’ordre des choses, suscitant des rencontres originales entre l’art et le politiqu

De la cuisine au studio : le rapport public/privé interrogé au fil des parcours d'artistes québécoises de trois générations - Lupien, Anna (Université du Québec à Montréal, 2011)

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

« Un studio à soi ». Entrevue avec Bérengère Marin Dubuard, du Studio XX - Parent, Sylvie (ETC, 2008)
Un article de la revue ETC, diffusée par la plateforme Érudit.

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
Dans l’introduction à ce numéro spécial d’Intersections, Andra McCartney et Ellen Waterman présentent les Dedans et Dehors du Studio, un projet de recherche ethnographique inter-universitaire soutenu financièrement par le CRSH du Canada de 2001 à 2005. L’équipe de recherche a étudié les idées et pratiques des artisans sonores canadiens, se penchant particulièrement sur le sujet de la relative invisibilité et inaudibilité des femmes, réfléchissant aux différentes manières dont les technologies et pratiques sonores peuvent être orientées sexuellement. Dans leurs essais, les auteures discutent des relations trouvées entre les termes genre, son et technologie, du point de vue aussi bien terminologique, qu’esthétique, du mentorat, ou encore méthodologique et théorique. Les contributions de McCartney, Diamond, Laplante, Labrosse, Marsh et Bosma sont ici discutées.

C'était du spectacle! L'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Le quartier chaud de Montréal a fait couler beaucoup d'encre, mais sa culture de cabaret n'a jamais été examinée dans la perspective des artistes transsexuelles et travesties qui l'ont rendu si populaire. Par le biais des récits provenant des danseuses elles-mêmes, Viviane Namaste peint un portrait honnête de quatorze transsexuelles - danseuses, chanteuses, magiciennes ou effeuilleuses - et jette un regard dans les coulisses du monde dans lequel vivent et travaillent ces hommes devenus femmes. Les années soixante et soixante-dix ont été des décennies de changement social au Québec. C'était du spectacle! raconte l'histoire de la première génération de transsexuelles ayant subi une chirurgie d'inversion de sexe. Namaste examine les conditions de travail dans les cabarets, la prostitution, les abus de pouvoir des policiers à l'égard des transsexuelles, le rôle du crime organisé dans la vie nocturne de la ville et l'accès aux soins de la santé. C'était du spectacle! offre un rare survol de la culture urbaine de Montréal, présenté dans ses propres mots par l'une de ses plus importantes communautés artistiques.

Considering Complexity in Canadian Civil Society: A Case Study of Studio XX - Gerlach, Neil; Hamilton, Sheryl (Revista Mexicana de Estudios Canadienses, 2002)

Virtually Civil: Studio XX, Feminist Voices, and Digital Technology in Canadian Civil Society - Gerlach, Neil; Hamilton, Sheryl N. (Civic Discourse and Cultural Politics in Canada, 2002)

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)

Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)